EFFICIENCY OF PORK PRODUCTION AT DIFFERENT PERIODS OF PIGS REARING AND THEIR RESISTANCE - Yaremchuk , O. (EurasianUnionScientists, 2021)
It was found that sows fed by Hliutam 1M for 3 days from the second day of insemination had 96.6% fertility, it was by 13.3% more than in the control. The feed additive effect on energy metabolism of piglets in the period of weaning from sows was studied. It was found that the supplement Humilid causes an increased glucose concentration, increased activity of alkaline phosphatase and creatine kinase within the physiological norm in the blood plasma of experimental group animals. These data indicate the intensification of energy metabolism and stimulation of phosphorylation processes under the feed additive influence of the addition. The obtained results are relevant for increasing the adaptability of piglets. The efficiency of soybean meal was proved due to the increase of its relative amount in the structure of the diet, it leads to an increase in the average daily gain of live weight of pigs by 1 kg or more reducing the time of their fattening. Resistance and productivity of replacement pigs brought from other farms of Vinnytsia region and reared in the industrial complex is genetically feasible and increases the resistance of offspring and their productivity.